ANALISIS METODE PEMBELAJARAN STEAM DALAM PERKEMBANGAN KOGNITIF ANAK USIA DINI - Dinta Ismaya Kurinci; Sakinah Siregar; Nidaun Nabila (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
Early age is an important period for children to develop, especially in children's cognitive development. Cognitive processes are closely related to the level of intelligence which refers to thinking, knowledge, and reasoning where this cognitive concerns the development of children's thinking. To improve aspects of cognitive development at an early age, one of them is by using the STEAM learning model. STEAM is a learning approach that is based on the relationship of knowledge and skills of science, technology, engineering, art, and mathematics (STEAM) to solve problems. Therefore, the purpose of this study is to analyze the STEAM learning model in early childhood cognitive development. This study uses qualitative methods and data collection techniques using the library method by collecting several journals and articles related to STEAM learning.